American Indians and the rhetoric of removal and allotment - Black, Jason Edward (Jackson [Mississippi] : University Press of Mississippi, 2015)
"Jason Edward Black examines the ways the US government's rhetoric and American Indian responses contributed to the policies of Native-US relations throughout the nineteenth century's removal and allotment eras. Black shows how these discourses together constructed the perception of the US government and of American Indian communities. Such interactions--though certainly not equal--illustrated the hybrid nature of Native-US rhetoric in the nineteenth century. Both governmental, colonizing discourse and indigenous, decolonizing discourse shaped arguments, constructions of identity, and rhetoric in the colonial relationship. American Indians and the Rhetoric of Removal and Allotment demonstrates how American Indians decolonized dominant rhetoric through impeding removal and allotment policies. By turning around the US government's narrative and inventing their own tactics, American Indian communities helped restyle their own identities as well as the government's. During the first third of the twentieth century, American Indians lobbied for the successful passage of the Indian Citizenship Act of 1924 and the Indian New Deal of 1934, changing the relationship once again. In the end, Native communities were granted increased rhetorical power through decolonization, though the US government retained an undeniable colonial influence through its territorial management of Natives. The Indian Citizenship Act and the Indian New Deal--as the conclusion of this book indicates--are emblematic of the prevalence of the duality of US citizenship that fused American Indians to the nation, yet segregated them on reservations. This duality of inclusion and exclusion grew incrementally and persists now, as a lasting effect of nineteenth-century Native-US rhetorical relations"--
Introduction: Colonization and Decolonization in the Native-US Relationship -- The Ties That Colonize : Rhetoric from Nationhood to Removal -- Governmental Colonizing Rhetoric During Indian Removal -- Native Decolonial Resistance to Removal -- Colonization and the Solidification of Identities in the General Allotment Act -- Pan-Indianism and Decolonial Challenges to Allotment -- Conclusion: Identity Duality and the Legacies of Colonizing and Decolonizing Rhetoric.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on June 10, 2015).
JSTOR
Keywords: United States; General Allotment Act (United States : 1887); Indians of North America -- Government relations -- History -- 19th century; Indians of North America -- Government relations -- History -- 20th century; Rhetoric -- Political aspects -- United States -- History -- 19th century; Rhetoric -- Political aspects -- United States -- History -- 20th century; Indian Removal, 1813-1903.; Indians of North America -- Legal status, laws, etc; Decolonization -- United States -- History; Citizenship -- United States -- History; Indians of North America -- Politics and government; Discours politique -- États-Unis -- Histoire -- 19e siècle.; Discours politique -- États-Unis -- Histoire -- 20e siècle.; Peuples autochtones -- États-Unis -- Déplacement, 1813-1903.; Décolonisation -- États-Unis -- Histoire; Peuples autochtones -- États-Unis -- Relations avec l'État -- Histoire -- 19e siècle.; Peuples autochtones -- États-Unis -- Relations avec l'État -- Histoire -- 20e siècle.; HISTORY -- Native American; SOCIAL SCIENCE -- Ethnic Studies -- Native American Studies; LANGUAGE ARTS & DISCIPLINES -- Rhetoric; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; Citizenship; Decolonization; Indians of North America -- Government relations; Indians of North America -- Legal status, laws, etc; Indians of North America -- Politics and government; Rhetoric -- Political aspects; United States; 1800-1999; History